Democracy and the Media—Revisited - Blumler, Jay G.; Coleman, Stephen (Javnost-The Public, 2015)
The model which dominated twentieth-century analysis of political communication systems is now out of date in many respects. Essential in the authors’ view is a reconsideration of some of the foundational concepts of political communication scholarship. They propose fresh lines of thought on: a communication-sensitive definition of democracy; the purposes of civic communication; evaluations of media roles in terms of those purposes; the politics–media axis; and new citizen roles in new-media conditions. Noting that values are always at stake in how political communication is organised, practiced and received, they distinguish two different conceptualisations of researchers’ policy roles for harnessing and enhancing communication, citizenship and democracy—as a visionary destination and as a journey towards it, respectively. They conclude that both deserve prominent positions on academic road maps.